Semi-quantitative analysis of formaldehyde in food using calibration chart based on number of colored wells of microwell plate titration - Mintra Tongdee; Prapin Wilairat; Wiboon Praditweangkum; Rattikan Chantiwas (My University, 2024)
Microplate titration quantifies sodium hydroxide generated from formaldehyde reacting with excess sulfite in a 96-microwell plate. Phenolphthalein indicators change from red to colorless when all hydroxide ions react. Methodology optimized reagent concentrations, and reaction time and created a Calibration Chart for semi-quantitative determination. The chart shows formaldehyde concentration ranges corresponding to red well counts from 0 to 200 mM in 20 mM increments. Inter-operator repeatability demonstrates precision (3 replicates), correlating red wells with standard formaldehyde concentrations. This instrument-free technique uses readily available commercial plates, eliminating the need for specialized equipment and calibration. The methodology offers simplicity with its reliance on readily available commercial plates and minimal specialized equipment, hence it is cost-effective and easily transportable 96-microwell plates enhancing the methodology's portability, and efficient semi-quantitative analysis of formaldehyde. The analysis of twelve solutions from food samples agrees with the quantitative values using titration.
Keywords: Sodium hydroxide; Phenolphthalein; Repeatability; Colored; Advanced Chemical Sensor Technologies